Bid or no bid decision making tool using analytic hierarchy process - Akalp, Duygu, author; Ozbek, Mehmet E., advisor; Senior, Bolivar, committee member; Atadero, Rebecca A., committee member (Colorado State University. Libraries, 2016)
In today's competitive business environment, every construction company confronts a decision-making dilemma and must decide whether to bid or not bid on a project(s) or which project(s) to bid on among candidates. Even though the decision-makers come to the conclusion with different judgments, a final evaluation always requires putting different factors into consideration and contemplating the ups and downs of a project. Therefore, bid or no bid decision is complex and crucial for construction companies. The complexity comes from the consideration of many intangible and tangible factors in the decision-making process (Mohanty 1992). Decision-making is hard because it requires a decision-maker to construct a structured thinking to include many unknown, yet complex variables and compare them simultaneously. Decision-making is crucial because poorly made bidding decisions could cause severe and irrevocable problems. For example, not bidding a favorable project could result in lost opportunities for companies to make profit, improve contractor's strength in the industry and gain a long-term relationship with a new client. On the other hand, bidding a project that actually does not fit the company's profile requires a lot of time, effort, and commitment without a favorable outcome (Ahmad 1990, Wanous et al. 2003). Given that "competitive bidding" is the most common bidding method in the construction industry among others (e.g., negotiated contracts, package deals, private finance initiative), investigating bidding strategies has been a focal point by researchers (Harris et al. 2006). Furthermore, more than 100 key factors that influence bidding decisions have been determined to date since the mid-1950s. Simultaneously, to expedite the process, numerous decision-making models have been proposed. Despite the excessive availability of the factors and decision-making models, the facilitation rate of the subsidiary tools in the evaluation process in the construction industry is very little. According to a survey by Ahmad & Minkarah (1988), only 11.1 percent of the construction companies use a decision making tool in order to come to a bid or not bid conclusion in the United States. The ultimate purpose of this study is to develop a practical decision-making tool to assist decision makers in the construction industry to select the most appropriate projects to bid on using Analytic Hierarchy Process (AHP). Based on the collected demographic information (e.g., sector, size, type), the combined importance weights of the construction professionals are also presented in the study. Finally, the statistically significant differences between different groups of construction companies in how much weight they assign to a given bid/no bid decision factor is investigated. In reaching the abovementioned purpose, the following questions are addressed: • What are the most common key factors that influence bid/no bid decisions? • How can different judgments from different decision-makers be combined into one final decision? • How differently the construction companies in the United States (US) value the key factors that are commonly utilized to make bid/no bid decisions? The validation of the bid/no bid decision-making tool was performed based on two participants' responses; and the tool provided accurate results for one of the evaluations. Because of insufficient response rate to the validation process, it cannot be concluded that the bid/no bid decision-making tool is validated; however the results of the participants point out the need for further research. The results showed that the compliance with the business plan and location of the project factors were found statistically significantly different for the "Contractor Type" classification. On the contrary, none of the key factors was found statistically significantly different for the "Contractor Sector" groups. For the "Contractor Size" classification, the compliance with the business plan factor was found statistically significantly different. The Group AHP approach allows construction companies to come with a combined bidding judgment instead of using the tool individually. As a major finding of this study is that, the contractors grouped under each construction classifications (i.e., Contractor Type, Contractor Sector and Contractor Size) put more value on the overall firm related-internal factors than the overall project related-external factors based on the Group AHP results. It is also found that the project duration and project size key factors have the lowest weights for all contractor classification groups. This study contributes to the construction engineering and management body of knowledge by providing an user friendly decision-making tool to be used in deciding whether to bid or not bid on a project or which project(s) to bid on and advancing the current state of the knowledge on the different weights/values given to the factors by construction companies with different demographics.
Keywords: analytic hierarchy process; key factors; AHP; multi criteria decision-making; bidding